Colonoscopy in Automated Peritoneal Dialysis Patients: Value of Prophylactic Antibiotics: A Prospective Study on a Single Antibiotic. Issue 10 (October 2017) - Al-Hwiesh, Abdullah K.; Abdul-Rahman, Ibrahiem S.; Hussameldeen, Mohammad A.; Al-Audah, Nadia; Abdelrahman, Abdalla; Moaigel, Hala M.; El-Salamony, Tamer; Noor, Abdul-Salam; Al-Osail, Aisha; Al-Sayel, Dalai; Al-Dossari, Nourah
Objective: To evaluate the need for prophylactic antibiotics in automated peritoneal dialysis (APD) patients undergoing flexible colonoscopy. Patients and Methods: A total of 93 patients on automated peritoneal dialysis (APD) undergoing diagnostic colonoscopy were enrolled in a prospective, randomized study. Patients were randomized into 2 age- and sex-matched groups; group A (46 patients) with intraperitoneal (IP) ceftazidime prior to colonoscopy and group B (47 patients) without prophylactic antibiotics. The relations between peritonitis and different parameters were analyzed. Results: Of all colonoscopies, 60.2% showed normal findings, 17.2% with colonic polyps at different sites, 12.9% with angiodysplastic-like lesions, 5.4% with colonic ulcer(s), 3.2% with diverticulae without diverticulitis and 1.1% had transverse colon stricture. Post-colonoscopy peritonitis was documented in 3 (6.5%) and 4 (8.5%) patients in groups A and B, respectively (p = 0.2742); the causative organisms were mainly gram negative bacteria. Polypectomy was not associated with increased peritonitis episodes. By multiple logistic regression analysis, diabetes mellitus was the only independent variable that entered into the best predictive equation over the development of post-colonoscopy peritonitis but not antibiotic use. Conclusions: The relation between prophylactic antibiotic use prior to colonoscopy in APD patients and the risk of peritonitis was lacking. Only diabetes mellitus appears to be of significance. Polypectomy did not increase peritonitis episodes.